Case report: Intracranial and spinal subarachnoid hemorrhage in a dog with Angiostrongylosis - Santifort, Koen M.; den Toom, Marjolein; Garosi, Laurent; Carrera, Ines (Frontiers in Veterinary Science, 2023)
A 1-year-old male intact Staffordshire terrier, born and raised in The Netherlands, was presented with a three-week history of progressive lethargy and spinal, predominantly cervical, hyperesthesia. Other than hyperthermia and cervical hyperesthesia, general and neurological examination did not reveal any abnormalities. Comprehensive hematological and biochemical tests were considered normal. Magnetic resonance imaging of the craniocervical region revealed heterogeneity of the subarachnoid space, characterized by pre-contrast T1W hyperintensity, corresponding to a T2* signal void. Extending from the caudal cranial fossa to the level of the third thoracic vertebra, there were uneven patchy extra-parenchymal lesions that caused mild spinal cord compression, most marked at the level of C2. At this level, the spinal cord showed an ill-defined hyperintense T2W intramedullary lesion. Mild intracranial and spinal meningeal contrast enhancement was evident on post-contrast T1W images. Subarachnoid hemorrhage was suspected and further diagnostic tests including Baermann coprology resulted in a diagnosis of hemorrhagic diathesis caused by an Angiostrongylus vasorum infection. The dog rapidly responded to treatment with corticosteroids, analgesic medication, and antiparasitic treatment. Follow-up over 6 months yielded complete clinical remission and repeatedly negative Baermann tests. This case report details clinical and magnetic resonance imaging findings in a dog with subarachnoid hemorrhage associated with an Angiostrongylus vasorum infection.